Level of Interest of Female Students at SMAN 1 Ambarawa to Participate in Extracurricular Futsal - Charis Dwi Churnaiwan; Ibnu Fatkhu Royana; Osa Maliki (LPPM Universitas PGRI Adi Buana Surabaya, 2024)
Futsal is a sport similar to football which is played indoors and played by 2 teams consisting of 5 people. The problem of this research is how interested female students of SMAN 1 AMBARAWA are in taking part in extracurricular futsal at school. This research aims to find out how interested female students at SMAN 1 AMBARAWA are in taking part in extracurricular futsal. This research is a quantitative descriptive research using a survey method. In this study, the sample used was class The data collection technique is in the form of a questionnaire using a Likert scale test. The research results will be further detailed into 2 factors, namely intrinsic and extrinsic. Where at 1). The intrinsic factor in the interest of female students at SMAN 1 Ambarawa to take part in extracurricular futsal can be categorized as very high with the number of students being 28 students, 56%. 2). External factors in the interest of female students at SMAN 1 Ambarawa Ambarawa to take part in futsal extracurriculars are in the very high category from 5 indicators including: a). Infrastructure facilities in the very high category with 43 female students (86%), b) environment in the high category with 26 female students (52%), c) Training indicators in the very high category with 37 female students (74%), d) Friends in the category very high with 34 female students (68%), e) Parents are in the very high category with 44 female students (88%) So it can be concluded that the interest of female students at SMAN 1 AMBARAWA in participating in futsal extracurriculars is in the very high category, which means the female students are very interested in take part in the futsal extracurricular that will be held